Designing of Flipped Classroom Approach to Teach Heat Transfer Course - Padmaja, A.; Sikindar Baba, Md. (Journal of Engineering Education Transformations, 2025)
In this paper we have designed flipped class room strategy for Heat Transfer course. As a first step towards flipping the class room three lessons are selected in the course. By delivering lecture content of selected topics before coming to class through videos and other media, class time is actively engaged in higher order thinking. The first step attempted is creating required Educational materials to transfer the delivery of content regarding the topics to an out of class environment. The second step is designing of active learning strategies Problem Solving, JIGSAW methods for the in class activity. Currently, limited research exists on the impact of the flipped classroom model in Engineering. A course such as Heat Transfer that involves design aspects and problem solving, requires time to teach concepts in an efficient and effective manner and can be best taught through flipped class approach. This paper would be definitely useful for all Mechanical&Chemical Engineering faculty members.